The Followers' Perception on The use of Twitter Auto-base Account @englishfess_ for Vocabulary Mastery - Afifah Riwi Maharani; Ainul Addinna (Universitas Negeri Padang, 2023)
Maharani, Afifah Riwi. (2023). The Followers’ Perception on the Use Of Twitter Auto- Base Account @Englishfess_ For Vocabulary Mastery. Undergraduate Thesis. Padang: English Language and Literature Department. Faculty of Languages and Arts. Universitas Negeri Padang. Social media such as Twitter have been popular among people as a alternative Media for Learning English. There is now a feature on Twitter called auto base that can be used to learn English. Twitter @englishfess_ is an account that uses the auto base feature, which allows any Twitter user to send messages anonymously via direct message containing questions or information about English. This study aims to know and describe Followers' perception on the use of Twitter Auto-base @englishfess_ for vocabulary mastery. The participants of this study were followers of @englishfess_ totaling 10 followers filled out questionnaires and interviews. In determining the participants, the researcher used purposive sampling technique. This study used a descriptive method with a qualitative approach. In collecting data, the researcher used questionnaires and interviews. Based on the results of this study, it was found that followers have a positive perception of using @englishfess_ to improve vocabulary. @englishfess_ shared various contents about English which can leads followers to add their vocabulary. Learning English on @englishfess_ is fun and less stressfull because is easy to access, varied Menfess vocabulary content, easy to understand, free and many others. As a result, @englishfess_ can be an interesting media for a follower who want to master their vocabulary and is a friendly account for followers who just want to learn English.